Exogenous Cellulase Contributes to Mycoherbicidal Activity of Fusarium arthrosporioides on Orobanche aegyptiaca - Olubukola O. Babalola (International Journal of Agronomy)
This paper investigates an association between the tubercle size of Orobanche aegyptiaca, tubercle death, and days to tubercle death in relation to cellulase-assisted mycoherbicide. Fusarium arthrosporioides killed 56% of tubercles when applied with cellulase compared to 35% when no cellulase was added. Death was inversely correlated with days over the two fungal treatment types. O. aegyptiaca tubercle size significantly correlated with the two other infection parameters studied. For F. arthrosporioides, only 9% (𝑟2) of the variation in days to death was explained by variation in tubercle size, whereas with cellulase it reaches 14%. In this study, mycelia of F. arthrosporioides did not show apparent damage to the tomato roots.